Uso de índices radiomorfométricos mandibulares na avaliação do dimorfismo sexual em indivíduos edêntulos totais - Ribeiro, Esther Carneiro (2021)
In the process of human identification, studies suggest the use of mandibular measurements, by means of panoramic radiographs (PR), to assess sexual dimorphism. Thus, this study aimed to assess whether the upper mandibular panoramic (PMS) and lower (PMI) indexes, and the mandibular alveolar bone resorption index (ROA) can be sex predictive measures. From these indices, it was also sought to realize and validate a formula for the analysis of sexual dimorphism in edentulous brazilian individuals. The study included 300 panoramic radiographs (RP) of total edentulous individuals, divided into the age groups: 51-60, 61-70 and 71-80 years. The measurements were performed by a single blind and previously trained evaluator, using the Inkscape® software. All statistical analyzes were performed using the IBM® SPSS® Statistics for Windows software, version 20.0, adopting a 95% confidence interval. Receiver Operating Characteristic (ROC) curves were constructed to estimate the cutoff points in the analysis of sexual dimorphism. The areas under the curve were also calculated, sensitivity, specificity, positive and negative predictive values, accuracy and likelihood ratio. The Mandibular Panoramic Index proved to be significant in predicting sex in the 71 to 80 age group, and when considering the mean of the sides, the PMS index was significant (p = 0.037). The ROA Index was significantly associated with gender. From the indices measured in the study, it was possible to create a formula for estimating sex in edentulous patients. This formula showed an accuracy of 61%, with values increasing with increasing age (72.0% for 61-70 and 80.0% for 71-80). To validate this formula, based on a sensitivity of 66% in predicting the male gender and a likelihood ratio of 6.00 (95% CI = 3.64-9.88) estimated by the formula of this study, it was necessary to evaluate 45 radiographs by sex. As a result of the validation, the predictive capacity of the formula was significant (p <0.001), with a sensitivity of 75.6%, and a specificity of 73.3%. Based on these results, the evaluated mandibular radiomorphometric indices can be predictors of sexual dimorphism through a formula for estimating sex in edentulous brazilian individuals.